What are the implications of variation in root hair length on tolerance to phosphorus deficiency in combination with water stress in barley (Hordeum vulgare)? - Brown, L.K.; George, T.S.; Thompson, J.A.; Wright, G.; Lyon, J.; Dupuy, L.; Hubbard, S.F.; White, P.J. (Annals of botany, 2012)
• Background and Aims Phosphorus commonly limits crop yield and is frequently applied as fertilizer; however, supplies of quality rock phosphate for fertilizer production are diminishing. Plants have evolved many mechanisms to increase their P-fertilizer use efficiency, and an understanding of these traits could result in improved long-term sustainability of agriculture. Here a mutant population is utilized to assess the impact of root hair length on P acquisition and yield under P-deficient conditions alone or when combined with drought. • Methods Mutants with various root hair phenotypes were grown in the glasshouse in pots filled with soil representing sufficient and deficient P treatments and, in one experiment, a range of water availability was also imposed. Plants were variously harvested at 7 d, 8 weeks and 14 weeks, and variables including root hair length, rhizosheath weight, biomass, P accumulation and yield were measured. • Key Results The results confirmed the robustness of the root hair phenotypes in soils and their relationship to rhizosheath production. The data demonstrated that root hair length is important for shoot P accumulation and biomass, while only the presence of root hairs is critical for yield. Root hair presence was also critical for tolerance to extreme combined P deficit and drought stress, with genotypes with no root hairs suffering extreme growth retardation in comparison with those with root hairs. • Conclusions The results suggest that although root hair length is not important for maintaining yield, the presence of root hairs is implicit to sustainable yield of barley under P-deficient conditions and when combined with extreme drought. Root hairs are a trait that should be maintained in future germplasm.